Transcriptomic–proteomic analysis reveals the regulatory mechanisms of Alfalfa (Medicago sativa) in response to Fusarium acuminatum - Shi, Zhidan; Sun, Hongxia; Hao, Lifen; Yang, Yongqing; Guo, Chen; Huangfu, Haiyan; Huo, Hongli; Zhao, Lili; Huangfu, Jiuru; Ding, Haijun; Fang, Yongyu; Li, Ziqin; et al. (Frontiers in Plant Science, 2025)
Alfalfa (Medicago sativa) is the most widely cultivated and important forage crop worldwide, owing to its high protein content. However, alfalfa Fusarium root rot seriously affects and restricts the yield and quality. This study explores the response mechanism of alfalfa to Fusarium root rot. we used transcriptomic and proteomic methods to analyze differentially expressed genes (DEGs) and differentially expressed proteins (DEPs) in alfalfa inoculated with Fusarium acuminatum on 0, 3, and 13 days. In total, 13,017 DEGs (6902 upregulated, 6115 downregulated) and 4830 DEPs (697 upregulated, 659 downregulated) were identified. Gene Ontology (GO) and Kyoto and Encyclopedia of Genes and Genomes (KEGG) analyses indicated that the DEGs and DEPs were mainly enriched in the cell cortex, flavonoid biosynthesis, and amino acid metabolism on day 3, whereas on day 13, they were primarily enriched in the cell wall, defense response, and flavonoid biosynthesis. Transcriptome and proteome analyses showed the same expression pattern of 81 genes and their corresponding proteins, which were mainly enriched in amino acid metabolism, cell wall synthesis, flavonoid biosynthesis, glucose metabolism, and plant-pathogen interactions. The results indicate that when alfalfa responds to infection by F. acuminatum, cell walls, antioxidant and defense-related enzymes, as well as genes involved in glucose metabolism and disease resistance, play important roles.This study contributes to the understanding of the molecular mechanism of the alfalfa response to F. acuminatum infection and provides an important basis for further research and in-depth characterization of candidate genes for breeding alfalfa root rot resistance.